2008
DOI: 10.1093/europace/eun350
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of home monitoring to reduce inappropriate shocks in implantable cardioverter-defibrillator patients due to lead failure

Abstract: In 91% of all lead-related ICD complications, the diagnosis could be established correctly by an alert of the HM system. Mostly, the first incident sent was oversensing of artefacts, falsely detected as ventricular fibrillation-the VF zone. The automatic HM surveillance system enables physicians to detect severe lead problems early and to react quickly; thus, it might have a potential to avoid inappropriate shocks due to lead failure and T-wave oversensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 10 publications
3
73
0
6
Order By: Relevance
“…However, overall, the potential benefit of RM is important not only in terms of hospital and social costs but also in terms of other potential advantages deriving from early diagnosis of device-related events such as lead failure or T-wave oversensing [22], and clinical events such as AF [10,23] or heart failure [5,7,8,11,24,25]. Moreover, these adverse events detected by RM are often silent [5] and, in the case of AF, occurred in about 30 % of the patients as new onset AF [23].…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overall, the potential benefit of RM is important not only in terms of hospital and social costs but also in terms of other potential advantages deriving from early diagnosis of device-related events such as lead failure or T-wave oversensing [22], and clinical events such as AF [10,23] or heart failure [5,7,8,11,24,25]. Moreover, these adverse events detected by RM are often silent [5] and, in the case of AF, occurred in about 30 % of the patients as new onset AF [23].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Moreover, these adverse events detected by RM are often silent [5] and, in the case of AF, occurred in about 30 % of the patients as new onset AF [23]. Such early diagnosis may reduce the rate of hospitalization and/or length of in-hospital stay [11], decrease the incidence of strokes [26,27], and reduce the number of inappropriate shocks causing early depletion of ICD therapy [20,22]. Such clinical benefit may result in an additional and even more important reduction of overall healthcare resource consumption, making RM economically attractive.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Twenty system-related complications required surgical intervention (remote vs. conventional, 15 vs. 5). In a retrospective cohort analysis of patients with an ICD lead failure, remote monitoring resulted in a significant reduction of inappropriate shocks and symptomatic pacing inhibition compared with those without remote monitoring (27% vs. 53%, P00.04) [21].…”
Section: Remote Monitoring Of System Integritymentioning
confidence: 96%
“…For early detection of lead failure, continuous monitoring of sensing values and especially the detection of episodes caused by electrical oversensing would be more helpful. Spencker et al [21] found that up to 90% of the patients with lead failure presented with …”
Section: Remote Monitoring Of System Integritymentioning
confidence: 99%
“…Small retrospective studies have found that in patients with ICD lead failure, inappropriate shocks were experienced in only 27% of patients using remote monitoring compared to 53% of patients with traditional follow-up. 11,12 The investigators estimated that remote follow-up identified problems 54 days earlier than traditional follow-up.…”
Section: Identification Of Device Hardware Problemsmentioning
confidence: 99%